Redispersible polymer powder modified cementitious tile adhesive as an alternative to ordinary cement-sand grout. Issue 11 (November 2021) - Bin Mobarak, Mashrafi; Hossain, Md. Sahadat; Mahmud, Monika; Ahmed, Samina
Abstract: With the advent of technologies on modern structural and building materials, adaptation of such technological features has been the pivotal concern of researchers. Ceramic tiles attained a distinctive focus due to its decorative feature for both indoor and outdoor conditions and also for their ease of implementation. The purpose of exploiting ceramic tiles is not only to impart structural strength but also the aesthetical characteristics that seem to matter a great deal. When it comes to the adhesion of these tiles onto the substrate wall, traditional method exerts the use of sand-cement grout. This faces some drawbacks including poor water retention property, hard and brittleness of the surface, much higher drying time, no flexibility, higher thickness of the paste and so on. These difficulties can be overcome by the addition of redispersible polymer powder (RPP) along with other cementitious constituents. The blended polymers interact with cement components to improve the physical and mechanical properties such as increased adhesion strength, reduced shrinkage and lower water absorption. This review article made an effort to provide the generalized idea about the cementitious tile adhesive (CTA) and its components. Focus was made onto the commercially available RPP and formulation of CTA with the inclusion of RPP. Critical analysis of the repercussions of RPP fortification was also carried out based on different researcher's findings. Abstract : Building material; Ceramic tiles; Tile adhesive; Redispersible polymer; Cementitious material.